KONSEP “PERIKHORESIS” DALAM PELAKSANAAN “GEREJA RUMAH” OLEH JEMAAT GMIT TALENALAIN DI TENGAH PANDEMI COVID-19 - Merensiana Hale; Eritrika Nulik (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2021)
The Covid-19 pandemic has had a profound impact on life, including the life of the church. The church requires the congregation to worship at home, not in the church building. This change in places of worship was followed by Christian families, particularly in the GMIT Talenalain congregation, although there were differences of opinion. Even though they worship at home, they miss worship in the church building. The theological understanding of home churches influences the difference in views about places of worship during the Covid-19 pandemic. This paper aims to show fluid or practical-operative ecclesiological concepts for the congregation during this pandemic. The extent to which the Christian family lives the concept of perichoresis in implementing the home church. This research uses a case study qualitative research method. The results show that the family interprets the home church as a communion of perichoresis Trinitarian praxis because it contains perichoretic values.